Peran dan Hambatan Stakeholders Dalam Penyediaan Fasilitas Dan Aksesibilita Pariwisata Bagi Wisatawan Disabilitas - kesami, Priti Nariya; Arismayanti, Ni Ketut; Sari, Ni Putu Ratna (Jurnal Kepariwisataan dan Hospitalitas, 2021)
Tourism is a foreign exchange producer that has great potential to be developed in addition to other sector. The tourism industry is generally the mainstay of economy in every country and city. One of the cities that make tourism as a mainstay sector is a Denpasar City. In line with the phrase from UNWTO as a tourism organization, Denpasar City as a tourist city able to provide facilities and accesibility no only for general tourist, disabled tourist can use. Denpasar City determined as an inclusion city by UNESCO in 2014 with 15 other cities. Denpasar City became an inclusion city due to the role of stakeholder in providing facilities and accessibility. The purpose of this reasearch was to determine the role of each stakeholder in provide facilities and accessibility for disabled tourist and stakeholder barriers in provide fcilities and accesibility. The research used descriptive qualitative method with observation, documentasion and indepth inteview method. The Informan in this information in this research used purposive samling method.   The result of this research showed roles of stakeholder interest in providing facilities and accessibility for disabled tourist in Denpasar City divinded into three categories besed on their identification primery, key and secondary stakeholder. while reviewed based on the influence of level of stakeholder interest in providing facilities and accessibility key stakeholder,Crowed stakeholder and Contest Setter stakeholder . while  stakeholder berries providing facilities and accessibility for disabled tourist is no data collection regarding disability tourist, the mindset of the community in the community regarding facilities and accesibility for disabled tourist and regulation cooperation among stakeholder. Based on the results of research suggestions is especially for goverment in the future can be record disability tourist so they can establish wisdom. Besides that there need to be good cooperation between the goverment and the private sector or with the organization can provide complate and easy information to disability tourist especially in the tourism.     Keywords: Disabled Tourist, Stakeholder, Facilities and Accessibility, Denpasar City.